The Effect of Digital Media Use in Science Education in Elementary Schools: A Systematic Literature Review - Sartika Wulandari; Sumarno (Journal for Lesson and Learning Studies, 2026)
Science learning in elementary education still faces challenges, particularly students’ low understanding of abstract concepts and the suboptimal use of innovative learning media, which results in low motivation, engagement, and learning outcomes. This study aims to analyze and synthesize empirical evidence regarding the effectiveness of digital media in science learning through a Systematic Literature Review (SLR) approach. This study employs an SLR design by analyzing ten articles on the use of digital media in science learning among elementary school students. Data collection was conducted through the stages of identification, screening, and eligibility assessment, using Indonesian and English keywords. The data were analyzed using thematic synthesis techniques to identify patterns of findings and key contributions from the selected studies. The results show that digital media consistently enhances learning motivation, understanding of science concepts, scientific literacy, higher order thinking skills, and active student participation, while also helping to visualize abstract concepts into more concrete forms. In conclusion, digital media plays a strategic role in improving the quality of science learning. The implication is that teachers need to integrate digital media appropriately according to the learning material, and schools need to provide adequate facilities and training to support effective implementation.